Punjabis Indians in Iloilo City. - Acosa, Jenelie Aguirre
This study is about Punjabi migrants in Iloilo City. It focuses on the factors that influenced them to move to Iloilo City, their life, future prospects as well as difficulties encountered and adjustments taken in their stay in Iloilo City.